Carbon pricing and taxation: A review of approaches and development implications - Jodie Keane; Hazel Granger; Prachi Agarwal; Maximiliano Mendez Parra (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
Nowadays, all policy makers must engage with direct and indirect carbon pricing issues. However, the implications of different types of tools and methods to price carbon and support decarbonization deserve further attention in view of their development implications. Two aspects-revenue recycling and complementary policies-are critical when it comes to ensuring that carbon pricing and taxation measures are supportive of broader sustainable structural economic transformation and help to avoid a 'green squeeze'. As countries begin to develop their own national systems of carbon taxation, it is critical to embed within these the potential for revenue recycling to address distributional issues, and to provide funding for complementary policies to support green transition and sustainable development endeavours. The major challenge at present is that mechanisms for effective redistribution are nascent or non-existent including across the case studies reviewed in this scoping study, i.e. South Africa, Mozambique, Ghana, and selected Latin American countries. Moreover, there are uncertainties regarding effective redistribution systems at an international level, with a continued failure to agree common approaches to pricing and reporting and verifying embedded carbon.
Keywords: F13; F53; D04; Q58; 330; carbon pricing; carbon taxation; revenue recycling; redistribution